Artykuł oryginalny Comparison of in-hospital and mid-term outcomes of percutaneous coronary intervention between patients aged over 65 and younger - Poorhosseini, Hamidreza; Sadeghian, Saeed; Abbasi, Kayvan; Hosseini, Kianoosh; Abbasi, Seyed Hesameddin; Sharafi, Ahmad; Abbasi, Ali; Shafiee, Nahid; Nematipoor, Ebrahim; Fathollahi, Mahmud Sheikh (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2009)
Background and aim: Advanced age is known to be correlated with adverse outcomes in patients undergoing percutaneous coronary intervention (PCI). We compared the outcomes of PCI between patients over the age of 65 and those younger. Methods: From a total of 5572 patients in the Tehran Heart Center PCI Registry,1318 (23.7%) persons > 65 years old (group I) were compared with 4254 patients Ł 65 years of age (group II) in a two-year period (April 2003 to June 2005). PCI outcomes were classified into in-hospital and mid-term. The in-hospital outcomes comprised major adverse cardiac events (MACE); including non-fatal myocardial infarction (NFMI), cardiac death, and emergent coronary artery bypass grafting (CABG). The mid-term outcomes consisted of MACE, target vessel revascularization (TVR), and target lesion revascularization (TLR). Results: Two patients in group I and 6 in group II suffered in-hospital MI (0.2 vs. 0.1%, p = 0.999). Both groups had the same rate of in-hospital death. With respect to the mid-term outcomes, a comparison between the two groups yielded the following results: NFMI: 2.2 vs. 1.0%, p < 0.001; CABG: 1.2 vs. 1.5%, p = 0.436; TVR: 2.0 vs. 2.6%, p = 0.205; TLR: 0.8 vs. 1.1%, p = 0.413; cardiac death: 1.4 vs. 0.3%, p 65 years) at mid-term follow-up, whereas there were no statistically significant differences between the two groups in terms of TVR, TLR, CABG, and MACE. Conclusion: The in-hospital outcomes were similar between the two groups. Those of advanced years (group I), however, had significantly higher NFMI and cardiac death rates than did the younger patients (group II) at mid-term follow-up.